The Risks of Forceful Feeding: Lentil Soup Aspiration and Its Association to Hypersensitivity Pneumonitis (HP) in Weaning Young Children - Habib, Rahat Bin; Kabir, ARM Luthful (The Journal of Ad-din Women's Medical College, 2025)
Forceful feeding practices, especially during the weaning period, are prevalent in South Asian countries, such as Bangladesh, where lentil soup is commonly introduced to young children. However, this practice can lead to accidental aspiration of food, resulting in hypersensitivity pneumonitis (HP), an immune-mediated inflammatory lung disease. This article explores the association between lentil soup aspiration due to forceful feeding and HP in pediatric patients. The pathophysiology of HP involves immune complex-mediated (Type III) and delayed-type hypersensitivity (Type IV) reactions, triggering inflammatory responses in the lungs, which may lead to chronic inflammation and fibrosis. Case studies reveal that male infants are particularly vulnerable, as their anatomical characteristics increase the likelihood of retaining aspirated particles in the lungs, which can result in granuloma formation and fibrotic lesions. Clinical features of aspiration pneumonia include persistent cough, fever, and dyspnea. Investigations such as chest radiographs, high resolution computed tomography, and bronchoalveolar lavage are essential for diagnosis, revealing typical radiological patterns and granulomatous inflammation. Treatment includes corticosteroids, proton pump inhibitors, and prokinetic agents, along with preventive strategies focusing on safe feeding practices. Educating caregivers about proper feeding techniques is crucial in preventing aspiration pneumonia and ensuring long-term respiratory health for children. The Journal of Ad-din Women's Medical College; Vol. 13 (1), Jan 2025; p 31-36